Characteristics and associated factors of preterm birth at Hospital Universiti Sains Malaysia (HUSM) in 2016 - Damanhuri, Narisa Hatun Ahmad (2018)
Background: Worldwide, preterm birth remains a significant public health threat in view of its increasing trend and devastating health effects. Similarly, in Malaysia the proportions of preterm birth and related neonatal death were observed to be rising since 2011. However to date, there are limited publications on local preterm birth specifically on its characteristics and associated factors. Objectives: The study aimed to investigate on preterm birth in terms of its characteristics and associated factors at HUSM in 2016. Methodology: Retrospective record review on secondary data was conducted by means of a cross-sectional study design in Part I (n=4,246) and a case-control study design in Part II (n=472). Data on mothers attending HUSM for deliveries in 2016 were extracted from the iMOMz database. Descriptive analysis was used in Part I to determine the proportions of preterm births and the proportions of preterm births based on its characteristics (sub-categories, types and neonatal outcomes). Univariate and multivariate analyses were used in Part II to identify the associated factors of preterm birth. Results: The proportion of preterm birth among live births at HUSM in 2016 was 6.5%. All of the preterm births (n=278) fell under the sub-category of moderate to late preterm and predominantly were spontaneous type (74.5%). Only 1.8% of the neonates of these preterm births died within the first 28 days of their lives. The presence of hypertension was significantly associated with preterm birth. Motherswith hypertension had 2.46 higher odds to experience preterm birth compared to mothers with no hypertension when adjusted for mothers with red-tagging (OR=2.46, 95% CI: (1.06, 5.72), p=0.037). Additionally, the presence of red-tagging was also significantly associated with preterm birth. Mothers with red-tagging had 2.06 higher odds to experience preterm birth compared to mothers with no red-tagging when adjusted for mother with hypertension (OR=2.06, 95% CI: (1.37, 3.10), p=0.001). Conclusion: There were significant associations between hypertension and red-tagging with preterm birth. Thus, optimising blood pressure control prior to and during pregnancy as well as preventing the occurrence of pre-eclampsia and its progression to eclampsia are essentially some of the recommended measures, which may improve pregnancy outcomes and reduce the preterm birth rate. In this study however, the model of fitness suggests that it has limited use for prediction. Therefore, future studies need to include all other risk factor variables which were not studied as these variables may improve the internal validity and outcome of studies on predictive risk factors of preterm birth.